Hereditary angioedema: the plasma contact system out of control. (17th July 2018) - De Maat, S.; Hofman, Z. L. M.; Maas, C.
Abstract : Summary: The plasma contact system contributes to thrombosis in experimental models. Even though our standard blood coagulation tests are prolonged when plasma lacks contact factors, this enzyme system appears to have a minor (if any) role in hemostasis. In this review, we explore the clinical phenotype of C1 esterase inhibitor (C1‐INH) deficiency. C1‐INH is the key plasma inhibitor of the contact system enzymes, and its deficiency causes hereditary angioedema (HAE). This inflammatory disorder is characterized by recurrent aggressive attacks of tissue swelling that occur at unpredictable locations throughout the body. Bradykinin, which is considered to be a byproduct of the plasma contact system during in vitro coagulation, is the main disease mediator in HAE. Surprisingly, there is little evidence for thrombotic events in HAE patients, suggesting mechanistic uncoupling from the intrinsic pathway of coagulation. In addition, it is questionable whether a surface is responsible for contact system activation in HAE. In this review, we discuss the clinical phenotype, disease modifiers and diagnostic challenges of HAE. We subsequently describe the underlying biochemical mechanisms and contributing disease mediators. Furthermore, we review three types of HAE that are not caused by C1‐INH inhibitor deficiency. Finally, we propose a central enzymatic axis that we hypothesize to be responsible for bradykinin production in health and disease.